2012
DOI: 10.1007/s00280-012-1980-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of active products of benzaldehyde dimethane sulfonate (NSC 281612, DMS612) in human blood and plasma and their activity against renal cell carcinoma lines

Abstract: Benzaldehyde dimethane sulfonate (BEN, DMS612, NSC281612) is an alkylating agent with activity against renal cell carcinoma and is being evaluated clinically. To support clinical trials, we developed an LC–MS/MS assay to detect and quantitate BEN and its metabolites/decomposition products. We tested the stability and products of BEN and benzoic acid dimethane sulfonate (BA) in plasma, blood and five renal carcinoma cell lines in vitro. Further, we determined the IC50 of BEN, BA and four of their products in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…We studied the metabolism of BEN in five different RCC lines and found that the ALDH activity correlated with the amount of BA-OH 2 generated [12]. This further supported for the idea that the conversion of BEN to BA is enzymatic.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…We studied the metabolism of BEN in five different RCC lines and found that the ALDH activity correlated with the amount of BA-OH 2 generated [12]. This further supported for the idea that the conversion of BEN to BA is enzymatic.…”
Section: Introductionmentioning
confidence: 64%
“…BEN has structural similarities to both busulfan and melphalan. As with related alkylators, we have previously shown that BEN undergoes hydrolysis in blood and plasma [12]. In whole blood, but not in plasma, BEN is rapidly converted to its carboxylic acid analogue BA, suggesting conversion by an enzyme present in red blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations